Nikah Dini: Pelembagaan Praktik Kekerasan Terhadap Perempuan - Wahyuni, Budi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
This article addresses the issues of child marriages from the perspective of an activist in women's empowerment. The practice of child marriage has become a medium for institutionalizingviolence against women. This is because the practice has violated some basic human's rights of young girls; such as their rights to education, to have opinion and to express their thoughts, to have their thoughts be heard, to rest and play, and to grow fully and be prgtected.